Perbandingan Kadar Flavonoid Dan Aktivitas Antioksidan Ekstrak Etanol Dan Infusa Daun Rambutan (Nephelium lappaceum L.) Dengan Metode ABTS - Aini, Riszki Nur; Listyani, Tiara Ajeng; Raharjo, Danang (Jurnal Ilmiah Wahana Pendidikan, 2023)
Free radicals in the body are very reactive and have oxidation reactions with certain body parts and cells which can trigger various diseases. Antioxidants are substances the body needs to neutralize free radicals and prevent free radical damage to normal cells, proteins, fats and antioxidants. This study aims to determine the content of flavonoids, secondary metabolite compounds and determine the antioxidant activity of ethanol extract and infusion of rambutan leaves (Nephelium lappaceum L.) which were tested using the ABTS method. Making ethanol extract using the maceration method with 96% ethanol solvent. Making infusion extract using distilled water as a solvent. Phytochemical screening tests were carried out using the tube test and TLC methods, determination of total flavonoid levels was carried out using the AlCl3 colorimetric method, antioxidant activity testing was carried out using the ABTS method. The research results showed that the ethanol extract of rambutan leaves (Nephelium lappaceum L.) contained alkaloids, flavonoids, saponins, tannins, triterpenoids and steroids with an average total flavonoid content of 23,390 mg QE/g. Rambutan leaf infusion extract (Nephelium lappaceum L.) contains alkaloids, flavonoids, tannins, triterpenoids and steroids with an average total flavonoid content of 12.294 mg QE/g. The test results show that the ethanol extract has antioxidant activity with an IC50 value of 59,250 ppm (Strong) and an IC50 value of 97,357 ppm (Strong). Ethanol extract has higher flavonoid levels compared to infusion extract. Ethanol extract has stronger antioxidant activity compared to infusion extract.